Integration of information and communication technology (ICT) in the development of a recordkeeping database of smallholder sheep farming systems in the Western Cape Province of South Africa - Chiwawa, Trust (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.